PENGARUH KECERDASAN EMOSIONAL DAN LINGKUNGAN BELAJAR DENGAN SELF-EFFICACY SEBAGAI VARIABEL MEDIASI TERHADAP KETERAMPILAN KOMUNIKASI PADA MAHASISWA PENDIDIKAN ADMINISTRASI PERKANTORAN ANGKATAN 2024 - Wikoyatur Rofikhoh; Tusyanah Tusyanah (Jurnal Manajemen Pendidikan, 2026)
Objective: This study aims to analyze the influence of emotional intelligence and the learning environment on communication skills, with self-efficacy as a mediating variable, among students in the Office Administration Education program at Universitas Negeri Semarang. The study population and sample consisted of 116 students from the class of 2024, selected using a saturation sampling technique. Data collection was conducted through questionnaires and documentation, then analyzed using descriptive statistics, inferential statistics, and hypothesis testing with the assistance of SmartPLS 4.0. The results of the study show that emotional intelligence, the learning environment, and self-efficacy have a positive and significant effect on communication skills. Additionally, emotional intelligence and the learning environment also have a positive and significant effect on self-efficacy. Self-efficacy mediates the influence of emotional intelligence and the learning environment on students’ communication skills. The analysis results show an R-square value of 78.6% for communication skills and 63.4% for self-efficacy, leading to the conclusion that the research model has a strong ability to explain the relationships among the study variables.